1999
DOI: 10.1021/bi990713y
|View full text |Cite
|
Sign up to set email alerts
|

Structural Change of Threonine 89 upon Photoisomerization in Bacteriorhodopsin As Revealed by Polarized FTIR Spectroscopy

Abstract: The all-trans to 13-cis photoisomerization of the retinal chromophore of bacteriorhodopsin occurs selectively, efficiently, and on an ultrafast time scale. The reaction is facilitated by the surrounding protein matrix which undergoes further structural changes during the proton-transporting reaction cycle. Low-temperature polarized Fourier transform infrared difference spectra between bacteriorhodopsin and the K intermediate provide the possibility to investigate such structural changes, by probing O-H and N-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
109
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(122 citation statements)
references
References 55 publications
11
109
2
Order By: Relevance
“…L- [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] O]threonine was synthesized as described (25). [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] O]threonine-labeled BR was prepared by growing Halobacterium salinarum (JW-3) in a defined medium similar to that described by Gochnauer and Kushner (26), except that the D-amino acids and NH 4 Cl were omitted and the L-threonine was replaced by 0.25 g͞liter L- [3-18 O]threonine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…L- [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] O]threonine was synthesized as described (25). [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] O]threonine-labeled BR was prepared by growing Halobacterium salinarum (JW-3) in a defined medium similar to that described by Gochnauer and Kushner (26), except that the D-amino acids and NH 4 Cl were omitted and the L-threonine was replaced by 0.25 g͞liter L- [3-18 O]threonine.…”
Section: Methodsmentioning
confidence: 99%
“…Polarized FTIR spectroscopy was applied as described (23,25). A 120-l aliquot of the sample in 2 mM phosphate buffer (pH 7.0) was dried on a BaF 2 window with diameter of 18 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, combined studies of isotopelabeled and mutant BR can lead to identification of particular vibrational bands. In fact, by use of 3-18 O-threonine-labeled BR and mutation of individual threonine residues, we showed that among 18 threonines in BR, only three, Thr-89 (26), Thr-17, and Thr-121 (or Thr-90) (27), change their hydrogen bonds in the K intermediate.…”
mentioning
confidence: 97%
“…) indicates a strong hydrogen bond (26). In K, a still lower stretching frequency (2,466 cm Ϫ1 ) corresponds to an even stronger hydrogen bond.…”
mentioning
confidence: 99%
“…were assigned to the O-H stretching vibrations of Thr-17 and Thr-121, respectively (35,36). Corresponding bands seem to be present in BR-T. We tentatively assigned the band at 3518(Ϫ) cm Ϫ1 as the O-H stretch of introduced Thr-215 in BR-T.…”
mentioning
confidence: 99%